Manufacturing Productivity and FDI Externalities: is Small Beautiful? - Santos, Eleonora (2022)
The role of FDI as a vehicle for economic growth is debatable in practice. On the other hand, the size of the company and the technological groups can influence the occurrence and magnitude of FDI externalities. Thus, this article investigates the impact of firm size on the occurrence of foreign direct investment externalities in the Portuguese industry from 1995 to 2007, by technology groups, using panel data at the firm level. To this end, we estimate the TFP and regress it on a set of variables, including the foreign presence in the same sector, upstream and downstream. The results show that only (small and large) companies in scale-intensive industries; and small firms in science-based industries benefit from the positive externalities of FDI. This suggests that firm size can influence the occurrence of FDI externalities in the manufacturing sector, but only in some technology groups. Based on the results, investment policy recommendations are made.